Reliability and Concurrent Validity of a Markerless, Single Camera, Portable 3D Motion Capture System for Assessment of Glenohumeral Mobility. - Ofra Pottorf; Daniel Vapne; Jamie Ghigiarelli; Kaitlyn Haase (International Journal of Sports Physical Therapy)
# Introduction